As pessoas portadoras de necessidades especiais sob a luz da hermenêutica filosófica heideggeriana - João Ricardo Eustáquio Cardoso de Paiva (Revista Interdisciplinar de Direito, 2010)
This study addresses the philosophical hermeneutic principles applied to special ne-eds, using a methodology of the sources of the view adopted by Martin Heidegger called Dasein. Among the proposals, we will approach in an objective and subjective, some defini-tions as to what turns out to be a person with special needs and analyze some of the existing legal instruments that protect fundamental rights of individuals with special needs and their dignity human person. We will do a brief overview of the laws that focused on throughout history and in a superficial way, we will evaluate the effectiveness of rules that is being cur-rently used by the world society and its influence in light of philosophical hermeneutics and phenomenology.